Budi Iman Santoso Assessment (BISA): a model for predicting levator ani injury after vaginal delivery (Faculty of Medicine Universitas Indonesia, 2012)
Background: There have been no attempts or studies to integrate various risk factors that can be utilized to predict levator ani injury caused by vaginal delivery. This study was aimed to establish an index measurement system by using various risk factors for predicting levator ani injury in vaginal delivery. Methods: A prospective cohort was conducted at two hospitals in Jakarta between 2010 and 2011. The subjects were nulipara pregnant women without levator ani injury during pregnancy and vaginal birth. Levator ani injury was evaluated using 4D USG during pregnancy and three months after delivery. The variables studied were age, body mass index, mode of delivery, fetal birth weight, episiotomy, perineum rupture and duration of second stage labor. Prediction model was analyzed using logistic regression analysis. Results: There were 182 recruited subjects of which 124 subjects were eligible and only 104 subjects could be analyzed. Incidence of levator ani injury at three months after delivery was 15.4% (95% CI: 8.6-23%). Two prediction models were obtained. The first consisted of fetal birth weight (OR= 5.36, 95% CI: 1.08-26.59), episiotomy (OR= 5.41, 95% CI: 0.94-31.18), and duration of second stage labor (OR= 15.27, 95% CI: 3.15-73.96). The second model consisted of duration of second stage labor (OR= 9.51, 95% CI: 1.23-68.10) and perineum rupture (OR= 142.70, 95% CI: 14.13-1440.78). Conclusion: Fetal birth weight, episiotomy and duration of second stage labor could predict levator ani injury for model 1; while the variables of prediction for model 2 were duration of second stage labor and perineum rupture. (Med J Indones. 2012;21:102-7)